2021
DOI: 10.3390/ani11030712
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Rumen Microbiota Affect Metabolites, Immune Responses and Antioxidant Enzyme Activities of Sheep under Cold Stimulation

Abstract: Low-temperature environments can strongly affect the normal growth and health of livestock. In winter, cold weather can be accompanied by strong winds that aggravate the effects of cold on livestock. In this study, two experiments were conducted to investigate the effect of low temperature and/or wind speed on physiological indices, rumen microbiota, immune responses and oxidative stress in sheep. When sheep were exposed to cold temperature and/or stronger wind speeds, the average daily gain (ADG) decreased (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Rikenellaceae_RC9_gut_group was negatively correlated with RR and RT measured in the present study; whereas it correlated positively with propionic acid that had the greatest effect on the bacterial species distribution in the HT cows as shown by the RDA analysis. This is consistent with the fact that propionic acid, which is a substrate for gluconeogenesis, activates gluconeogenic gene expression to maintain energy homeostasis [43]. It is speculated that Rikenellaceae_RC9_gut_group plays an essential role in heat production and body temperature regulation in the HT cows, and promotes the recovery of the metabolic rate in heat stress environment.…”
Section: Discussionsupporting
confidence: 65%
“…Rikenellaceae_RC9_gut_group was negatively correlated with RR and RT measured in the present study; whereas it correlated positively with propionic acid that had the greatest effect on the bacterial species distribution in the HT cows as shown by the RDA analysis. This is consistent with the fact that propionic acid, which is a substrate for gluconeogenesis, activates gluconeogenic gene expression to maintain energy homeostasis [43]. It is speculated that Rikenellaceae_RC9_gut_group plays an essential role in heat production and body temperature regulation in the HT cows, and promotes the recovery of the metabolic rate in heat stress environment.…”
Section: Discussionsupporting
confidence: 65%
“…T-AOC, SOD, and GSH-Px in serum are all essential components of the antioxidant defense system, and they have very significant impacts on homeostasis between oxidation and antioxidants [ 63 ]; MDA is one of the end-products of lipid peroxidation, and its level reflects the degree of oxidative injury to the organism [ 64 ]. As reported, cold stress could cause an increase in T-AOC, SOD, and GSH-Px levels [ 65 ] and the reduction of MDA levels [ 66 ]. Previous studies reported that EUE improved the antioxidant capacity of weaned piglets [ 31 , 67 ].…”
Section: Discussionmentioning
confidence: 98%
“…The greatest effect was recorded in the cellulolytic population of the rumen. Rumen-based microbial attachment to fibrous substrates has been reported to be optimal at 39 • C; lower temperatures markedly reduce adhesion [15]. In fact, Petersen et al (2016), in a study conducted in vitro and in vivo, reported that in vitro NDF degradability decreased from 41 to 14% when the water-bath temperature, which reproduced the rumen environment, decreased from 39 to 31 • C. However, these results were not confirmed in vivo because the duration of time in which the rumen temperature was below 38 • C was not sufficient to reduce NDF degradation [17].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in rumen temperature can alter microbial activity, reducing both the number of microbes and bacterial diversity, richness and functionality, leading to both poorer overall dry matter digestibility and poorer production of short-chain fatty acids [ 14 ]. Specifically, deviations in rumen temperature may impair fiber digestion [ 15 ].…”
Section: Introductionmentioning
confidence: 99%